Alcohol, tobacco and others drugs: nursing academic´s perception - Leão, Laís Monteiro Araújo Campos Arêa; Elias, Conceição de Maria Vaz; Branco, Fernanda Matos Fernandes Castelo; Monteiro, Claudete Ferreira de Souza (Revista de Pesquisa Cuidado é Fundamental Online, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><span style="font-size: 10.0pt; line-height: 150%; font-family: "Trebuchet MS","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Trebuchet MS"; color: black; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">Objectives:<span style="font-size: 10.0pt; line-height: 150%; font-family: "Trebuchet MS","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Trebuchet MS"; color: black; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US"> To understand the perception of nursing students about alcohol, tobacco and other drugs in the context of their academic training. Method: This is a descriptive study with a qualitative approach using as production technique of the interview data with 15 nursing students of a private institution of higher education. Results: Data were grouped into two categories: knowledge of graduating nursing students on alcohol, tobacco and other drugs and academic formation versus practical application. Conclusion: The study shows a predominance of some participants' knowledge of drugs with specific information, without a more profound reflection on the subject in question on the politics of confrontation and actions of nurses. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->